Effectiveness of flipped classroom practices in teaching of science: a mixed research synthesis - Dogan, Yunus; Batdi, Veli; Yasar, Mehmet Diyaddin (Routledge Journals, Taylor & Francis Ltd, 2023)
Background: Flipped classroom, which is inversion of conventional classroom procedures in simple terms, currently stands out as a popular teaching strategy for many Science courses. Purpose: In this article, we tried to make a reinterpretation of the findings of recent empirical studies conducted on the effectiveness of the flipped classroom approach in science education. Design and Methods: To determine the overall effect size of the flipped classroom implementations in Science courses, a meta-analysis of 30 studies with such moderator variables as education levels, durations of implementations, various subjects areas of science and class sizes was carried out. To consolidate the academic achievement theme dwelled on in the meta-analysis part, a meta-thematic analysis based on document analysis of qualitative studies was conducted to expound in detail general characteristics of the approach, its effect on academic dimension, its contribution to the affective domain and classroom environment. Results: The findings reveal that the flipped classroom implementations have a positive medium effect (g = 0.727) on academic achievement in Science classes. Physics and Chemistry classes have the highest effect size values while Biology has the lowest effect size; the flipped classroom practices proved best in small size classes and at Primary School level with the highest effect sizes. Conclusions: The findings of both analyses provide insights into applicability of the approach in teaching of Science and its sub-branches. The drawbacks of the approach are also discussed with some suggestions for implication.
Keywords: Flipped classroom; Science education; science; mixed research synthesis; meta-analysis; meta-thematic analysis